Massive bilateral mandibular metastasis from papillary thyroid carcinoma - Siti Asmat Md Arepen; Irfan Mohamad (Elsevier B.V., 2024)
Papillary thyroid carcinoma (PTC) comprises almost eighty percent of differentiated thyroid malignancy. It affects female more than male in the age range between 40–50 years old. It usually metastasizes to ipsilateral regional lymph nodes of neck and rarely have distant metastasis. Common route of dissemination of tumour is through lymphatic system. We reported a rare case of bilateral mandibular metastasis from incomplete resection of follicular variant of PTC.